SMARTPHONE APPLICATIONS FOR MEDICAL STUDENTS AND PROFESSIONALS - V., Vinay K.; K., Vishal (Journal of Health and Allied Sciences NU, 2013)
Mobile phones have been widely used for several decades, but the smartphones are a more recent advance. The latest generation of smartphones are increasingly viewed as handheld computers rather than as just phones, due to their powerful on-board computing capability and open operating systems that encourage application download and development. In a relatively short period of time, smartphone technology has penetrated significantly into society from school children to senior citizens. The level of smartphone usage by medical students and professionals is increasing day by day with the extensive availability of downloadable medical applications related to medical education and health. This article mentions about the useful and popular smartphone applications for medical students and practitioners which helps to integrate technology into clinical practice.
Keywords: Smart phone application; Mobile technology